ТЕХНОЛОГІЧНІ СЕНТЕНЦІЇ ГАРМОНІЙНОГО ЄДНАННЯ ТОЛЕРАНТНОЇ, ДУХОВНОЇ ТА ДУШЕВНОЇ АТМОСФЕРИ - ОСНОВА РОЗВИТКУ ЛЮДСЬКИХ ЦІННОСТЕЙ (Педагогіка вищої та середньої школи, 2010)
The article deals with technologic maxims of the harmonious unity of the tolerant, spiritual and emotional atmosphere as the basis of the development of human values.